2010
DOI: 10.1007/s11033-010-0550-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MicroRNA-143 in the differentiation and proliferation of bovine intramuscular preadipocytes

Abstract: The purpose of the present study was to investigate the regulation of propionate on the proliferation and differentiation of cultured intramuscular preadipocytes from three adult Luxi Yellow steers. The fl ow cytometry, lipid droplets stained by oil red O, and cytoplasmic fat content were detected after cultured cells were treated with different concentrations of propionate (0, 1, 3, 6 mM). The results showed that the separated cells were highly homogeneous and proliferative. Propionate (1 mM) did not signifi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 27 publications
3
39
0
1
Order By: Relevance
“…Expression of miR-143 is upregulated during differentiation of bovine intramuscular preadipocytes into mature adipocytes. Transfection of miR-143 antisense oligonucleotide represses the differentiation of bovine intramuscular preadipocytes (Li et al, 2011b). These observations further support a role of miR-143 in intramuscular fat development in cattle.…”
Section: Mirnas In Cattlesupporting
confidence: 68%
“…Expression of miR-143 is upregulated during differentiation of bovine intramuscular preadipocytes into mature adipocytes. Transfection of miR-143 antisense oligonucleotide represses the differentiation of bovine intramuscular preadipocytes (Li et al, 2011b). These observations further support a role of miR-143 in intramuscular fat development in cattle.…”
Section: Mirnas In Cattlesupporting
confidence: 68%
“…For the same duration of incubation, HeLa cells transfected with MALAT1 or the miRNA-143 inhibitor had elevated proliferative activity, and those transfected with miRNA-143 or the MALAT1 inhibitor showed lower proliferation, compared to that of the control transfected cells. These results suggested that the high levels of miRNA-143 and/or low levels of MALAT1 decreased the proliferation of HeLa cells, while low levels of miRNA-143 and high levels of MALAT1 might facilitate proliferation, consistent with previous studies revealing the negative regulation of miRNA-143 in cell proliferation (Li et al, 2011;Liu et al, 2016). Lajer et al (2012) suggested that miRNA-143 might participate in the pathogenesis of the disease in a way that is similar to that observed for human papilloma virus infection in patients with cervical cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The conversion of cells into adipocytes was confirmed by the detection of lipid droplets under microscopy using Oil Red O staining (Li et al, 2011). In briefly, cells were rinsed three times in PBS and then fixed in 4% (v/v) formaldehyde for 10 min, after which the fixed cells were rapidly rinsed with DPBS.…”
Section: Oil Red O Stainingmentioning
confidence: 99%